Current Scenario of Foot and Mouth Disease (FMD) at Dhanbari Upazila, Tangail, Bangladesh (Research in Agriculture Livestock and Fisheries, 2025)
Foot-and-mouth disease (FMD) is considered an economically devastating and highly contagious disease affecting both domestic and wild cloven-hoofed animals. It also poses a significant threat to the livestock industry in Bangladesh, impacting production and hindering trade. To address this concern, a study was conducted at Dhanbari Upazila, Tangail, Bangladesh, from October 5, 2022, to November 4, 2023. A total of 1071 cattle were examined, comprising 358 males and 713 females. The overall prevalence of FMD in Dhanbari Upazila was found to be 30.25%. The study investigated the influence of several factors, such as age, sex, breed, season, farming system, and vaccination, on the prevalence of FMD. Results indicated a significantly higher prevalence during winter (41.56%), with older cattle exhibiting a higher susceptibility (30.07%). Moreover, females were more susceptible (39.69%) than males (11.45%). The indigenous breeds were more prevalent (47.64%) than crossbreeds (19.76%). Additionally, a higher prevalence was found in non-vaccinated cattle (38.53%) than in vaccinated cattle (4.9%). Cattle from rural household farms have a higher prevalence (31.26%) compared to cattle from intensive farms (29.06%). Age, sex, breed, season, vaccination, and nutrition were significantly (p